Analisis Nilai Pendidikan Karakter Peduli Sosial Dalam Buku Siswa Kelas 3 SD Tema 4 Peduli Lingkungan Sosial - Wida Faradila; Arsyi Rizqia Amalia; Iis Nurasiah (STKIP Andi Matappa Pangkep, 2020)
This study aims to describe the values of character education contained in the 3rd grade students' books in theme 4 Caring for the Social Environment. This research is a qualitative descriptive study The data in this study are sentences that contain and show the value of social care character education. Data collection is documentation. Data analysis method used is content analysis. The results showed the value of character education of social care in accordance with the indicators, namely: (1) tolerant of differences, (2) able to work together, (3) willing to be involved in community activities, (4) love humans and living things, (5) love peace in dealing with differences. So there are indicators of the value of social care character education that has not been found in the sentences contained in the book grade 3 elementary school students theme 4 Caring for the Social Environment, namely: (1) treat others politely, (2) act politely, (3) do not like to hurt people others, (4) do not take advantage of others.